The Influence of Economic Growth, Dependency Ratio, Education Level, and Minimum Wage on Poverty Levels in Kebumen Regency - Ayuningtyas, Anisa Dwi; Imaningsih, Niniek (Journal of Business Management and Economic Development, 2024)
Poverty is an issue faced by both developing and developed countries. Like other developing countries, Indonesia continues to strive to overcome the problem of poverty in its territory which is an obstacle to economic development in the country itself. This research was conducted with the aim of determining the effect of Economic Growth, Dependency Ratio, Education Level, and Minimum Wage on Poverty Levels in Kebumen Regency during the period 2005-2022. The data used in this research is secondary data obtained from the Kebumen Regency Central Statistics Agency (BPS). The method used in this research is quantitative using multiple linear regression analysis with the BLUE assumption (Best Linear Unbiased Estimate). So that the results obtained simultaneously are Economic Growth, Dependency Ratio, Education Level, and Minimum Wage which together have an effect on Poverty Level, while partially the Economic Growth variable has a negative and insignificant effect, the Dependency Ratio variable has a negative and insignificant effect, the Education Level variable has a positive effect significant, and the Minimum Wage variable has a significant negative effect on the Poverty Level in Kebumen Regency.